How an Islamist party managed to legitimate its authoritarianization in the eyes of the secularist opposition: the case of Turkey. Issue 2 (17th February 2020) - Yilmaz, Ihsan; Caman, Mehmet Efe; Bashirov, Galib
ABSTRACT: Since at least 2011, Turkey has undergone a dual process of democratic backsliding amid the emergence of a new, authoritarian regime under the leadership of Recep Tayyip Erdoğan. An interesting component of this process of authoritarian turn has been the lack of serious opposition on the part of the opposition parties CHP and IYIP parties to the growing political repression, curtailment of civil liberties and growing consolidation of power in the hands of Erdoğan. In this article, we deal with a major puzzle that emerged in Turkey's politics: how did the AKP regime legitimize its authoritarian transformation of the political system in Turkey in the eyes of CHP and IYIP, despite these parties' political opposition to the AKP regime and its Islamist agenda? In answering this question, we make use of a causal theory that predicted the intensified use of legitimation claims on the part of the incumbent regimes during authoritarian restructuring. Combining the works of several scholars, we utilize the concept of "missions, " along with ideational narratives, performance objectives and six claims of legitimation to explain how the AKP managed to legitimize its authoritarian grip and regime change even in the eyes of the main opposition parties.